Medal count - the fate of nations at the Olympics. How national wealth, democratic government, genetics, immigration and sports accessibility enable athletic empowerment that explains Olympic success - Theuer, C. P. (Universal Publishers, 2025)
This book explores complex factors that determine Olympic success, exploring why certain nations consistently dominate the medal tables while others struggle to secure even a single medal. Dr. Theuer, a physician and epidemiologist, applies statistical analyses to uncover the national characteristics that drive Olympic achievement, focusing on measurable factors such as national wealth and democratic governance. But the book also examines less quantifiable influences - genetics, the impact of immigration, and sports accessibility - providing a multifaceted view of athletic empowerment. In a sense, the book explores human empowerment viewed through the lens of Olympic success.